Trace Elements Zinc and Selenium: Their Significance in the Conditions of the COVID-19 Pandemic - Gulich, M.P.; Yemchenko, N.L.; Kaplinenko, V.G.; Kharchenko, O.O.; Гуліч, М.П.; Ємченко, Н.Л.; Каплуненко, В.Г.; Харченко, О.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Within the conditions of the ongoing COVID-19 pandemic, when many questions regarding prevention and treatment strategies remain unsolved and the search for the best antiviral agents is underway, attention should be paid to the role of trace elements zinc and selenium in increasing the body’s resistance to viral infections and their direct antiviral activity against SARS-CoV-2. Experimental data show that trace elements zinc and selenium not only act through regulating the immune response at all levels of humoral and cellular immunity, but also can play a significant role in adjuvant therapy for viral diseases. This is especially relevant in the case of COVID-19. Studies of the direct antiviral effect of these microelements testify to its 3 main ways to SARS-CoV-2: I — counteraction to virus replication and its transcription through: (i) their covalent binding to the SH-group of the cysteine of the main protease M(Pro) of the virus; (ii) inhibition of its RNA polymerase activity by zinc; II — preventing the penetration of the virus into cells due to blocking SH-groups of protein disulfide isomerase (RDI) of the protein of its spikes (peplomers); III — decreasing the adsorption capacity of the virus due to the blocking of the electrostatic interaction of SARS-CoV-2 peplomers and angiotensin-converting enzyme (ACE-2) in ultra-low, uncharacteristic oxidation states (Zn+1 and Se-2). The intensity of the antiviral action of these trace elements may depend on their chemical form. It was found that zinc citrate (a five-membered complex of zinc with citric acid) and monoselenium citric acid obtained with the help of nanotechnology have a greater intensity of action and higher chemical purity. Taking into account the immunostimulating and direct antiviral effect of zinc and selenium, their use in the form of pharmaceuticals and dietary supplements should be considered as adjunctive therapy for SARS-CoV-2 in patients, or as a preventive strategy for uninfected people from risk groups during the spread of COVID-19.